IMPLEMENTASI MODEL (PAKEM) PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN TERHADAP MINAT BELAJAR BAHASA ARAB SISWA KELAS VIII MTS MUKHTAR SYAFAAT BANYUWANGI TAHUN AJARAN 2024 - 2025: MODEL (PAKEM) PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DAN MENYENANGKAN - syafiudin, muhammad (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2024)
Keywords: PAKEM model, Interest in learning, Arabic ABSTRACT : This research aims to determine the implementation of the Active, Creative, Effective, and Fun Learning (PAKEM) model on the interest in learning Arabic among eighth-grade students at MTS Mukhtar Syafaat Banyuwangi 2024-2025.This research is a type of field research, which can be referred to as field research with a qualitative approach. Data collection techniques include: observation guidelines, interview guidelines, and documentation. The subjects of this research are 10 students from the 8th grade of MTS Mukhtar Syafaat Banyuwangi and 1 Arabic language teacher, making a total of 11. Data analysis technique: the researcher first conducted data collection techniques, followed by data reduction, data presentation, and then drawing conclusions.The result of this research is generally the implementation of the Active, Creative, Effective, and Enjoyable Learning (PAKEM) model on the interest in learning Arabic among eighth-grade students at MTS Mukhtar Syafaat Banyuwangi. The researcher also found supporting and inhibiting factors in the implementation of the PAKEM strategy, due to several factors including the students' school background, and its advantages can be seen from the students' enthusiasm and active participation in their learning. This can be seen from the enthusiasm of the students and their active participation in Arabic language learning, as well as the interaction between teachers and students, among students themselves, teachers, and learning resources with the implementation of active, creative, effective, and enjoyable learning. الكلمات المفتاحية : نموذج PAKEM ، اهتمام التعلم، اللغة العربية مستخلص البحث: تهدف هذه الدراسة إلى معرفة تنفيذ نموذج (PAKEM) تعليم النشط والإبداعي والفعال والممتع على اهتمام التعلم اللغة العربية للطلاب في الصف الثامن مدرسة الثانوية مختار شفاعة بانيوانجي٢٠٢٤ – ٢٠٢٥. هذا البحث هو نوع من الأبحاث الميدانية باستخدام النهج النوعي. تقنية جمع البيانات هي: دليل الملاحظة، دليل المقابلة، والتوثيق. موضوع البحث هذا هو طلاب في الصف الثامن مدرسة الثانوية مختار شفاعة بانيووانجي. وعددهم ١٠ طلاب ومعلم لغة عربية واحد، ليكون المجموع ١١ أشخاص. تقنية تحليل البيانات التي استخدمها الباحث تشمل جمع البيانات أولاً، ثم تقليل البيانات، وعرض البيانات، وأخيراً استخلاص النتائج .نتائج هذا البحث هي بشكل عام تطبيق نموذج (PAKEM) التعلم النشط، الإبداعي، الفعال والممتع على اهتمام الطلاب في تعلم اللغة العربية في الصف الثامن مدرسة الثانوية مختار شفاعة بانيووانجي. وجد الباحثون أيضًا عوامل داعمة ومعيقة في تطبيق استراتيجية PAKEM، نظرًا لوجود عدة عوامل منها خلفية المدرسة الأصلية للطلاب، وأيضًا يمكن رؤية ميزاتها من خلال حماس الطلاب ونشاطهم في التعلم. يمكن رؤية ذلك من خلال حماس الطلاب ونشاطهم في تعلم اللغة العربية وكذلك التفاعل بين المعلم والطلاب، وبين الطلاب بعضهم البعض، وبين المعلم ومصادر التعلم، حيث يتم تطبيق التعلم النشط والإبداعي والفعال والممتع بشكل جيد.